Managing millennials for dummies - Ubl, Hannah L.; Walden, Lisa X.; Arbit, Debra (--For dummies., 2019)
Everything you need to harness Millennial potential Managing Millennials For Dummies is the field guide to people-management in the modern workplace. Packed with insight, advice, personal anecdotes, and practical guidance, this book shows you how to manage your Millennial workers and teach them how to manage themselves. You'll learn just what makes them tick-they're definitely not the workers of yesteryear-and how to uncover the deeply inspirational talent they have hiding not far below the surface. Best practices and proven strategies from Google, Netflix, LinkedIn, and other top employers provide real-world models for effective management, and new research on first-wave versus second-wave Millennials helps you parse the difference between your new hires and more experienced workers. You'll learn why flex time, social media, dress code, and organizational structure are shifting, and answer the all-important question: why won't they use the phone? Millennials are the product of a different time, with different values, different motivations, and different wants-and in the U.S., they now make up the majority of the workforce. This book shows you how to bring out their best and discover just how much they're really capable of.